Adaptive Use Situation for Urban Conservation in Thai Context - Pongsermpol, Chotewit (Asian Creative Architecture, Art and Design, 2012)
Abstract This study is a part of Literature Review in the research, Adaptive use policy improvement for urban conservation in Thai context, which author joined in Gottenheim Conference, International Journal of Arts and Science (JIAS) in Gottenheim, Germany on 4th December, 2008. The content is about urban building conservation in the changing social and economic situation, focusing on the background, adaptive use approach, valuing cultural heritage, regulation and organization concerned to adaptive use policy in Thailand and conclusion leading to next part of the research. Adaptive use policy improvement for urban conservation in Thai context, expressing background, objectives, research questions, scopes of research, literature reviews, methodologies and research outcomes. The study is about urban building conservation in the changing social and economic situation, focused on adaptive use of historic buildings and areas, adaptive use policy and procedure in Thailand comparing to international countries, building valuing and practical situation in Thailand, The objectives are to study the procedure and exact management of adaptive-reuse in Thailand comparing to the international standard, to รณdy valuing cultural heritages, sustainability in urban development, to find out the factors which impact to success of adaptive-reuse in urban historic conservation and to find out the guidelines for adaptive-reuse policy improvement in urban conservation for Thai context. The research questions are how the procedure of adaptive-reuse in Thailand is, what adaptive use approach that is harmonious to sustainability approach and how the adaptive-reuse policy improvement in urban conservation for Thai context should be. The scopes of research focus on urban heritage buildings which have adaptive-reuse. The literature reviews are cultural conservation approach, historical area management approach and adaptive use approach. The methodologies are studying literature review, the current situation of the adaptive use procedure in Thai context, factors which lead to the success of adaptive use in urban historic conservation, setting the criteria for case studies, collecting data, analyzing and concluding the research. And the research outcomes are to know about current situation of the adaptive use procedure in Thai context comparing to the international level, factors which lead to the success in implementing adaptive use in urban historic conservation and the guidelines for adaptive use policy improvement in urban conservation for Thai context. Keyword: Adaptive Use, Urban Conservation